Good Perinatal Outcome of Rhesus Incompatibility in Multigravida without Anti-D Injection Therapy: A Rare Case Report - Husada, Abdillah; Lestari, Peby Maulina; Maritska, Ziske; Sari, Dian Puspita; Al Farisi Sutrisno, Muhammad; Stevanny, Bella (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Rhesus (Rh) incompatibility problem arises exclusively when an Rh-positive male impregnates an Rh-negative female, resulting in maternal Rh sensitization to produce anti-D antibodies that can bind and destroy Rh-positive erythrocytes of the fetus. Hemolytic disease of the neonate due to Rh incompatibility ranges from self-limited hemolytic anemia to severe hydrops fetalis. Rh incompatibility can be prevented by administering anti-D injection therapy containing Rh Intravenous Immunoglobulin (RhIVIG). We report a rare case of good perinatal outcome of rhesus incompatibility in multigravida without anti-D therapy injection due to weak D phenotype.Case Illustration: A gravida 3, para 2 woman at 27 weeks gestation with Rh-negative blood type, who has not experienced any previous compatibility problems, came to our facility for routine antenatal care. The husband has an Rh-positive blood type with a Dd genotype (heterozygous), suggesting a 50% probability that the offspring will have an Rh-positive blood type. Laboratory results showed a negative Coombs test and weak D phenotype. The patient had never received an anti-D therapy injection in this pregnancy and her previous two pregnancies. None of her children developed hemolytic disease in the neonate. Ultrasonography showed a well-developed 27-week gestational age fetus with no major congenital disorders. The good perinatal outcomes of her children might be due to weak D phenotype. Pregnant women with weak D phenotype have fewer D antigens that can still result in Rh sensitization but not enough to cause serious complications to the fetus. Conclusion: Rhesus incompatibility with weak D phenotype can have good perinatal outcomes without anti-D injection therapy. Administration of Anti-D injection remains a viable option to prevent subsequent Rh alloimmunization.Inkompatibilitas Rhesus pada Multigravida dengan Luaran Perinatal Baik tanpa Terapi Injeksi Anti-D: Laporan KasusAbstrakPendahuluan: Masalah inkompatibilitas Rhesus (Rh) muncul secara eksklusif pada ayah Rh-positif dan ibu Rh-negatif, sehingga terjadi sensitisasi Rh ibu untuk menghasilkan antibodi anti-D yang dapat mengikat dan menghancurkan eritrosit janin yang Rh-positif. Penyakit hemolitik pada neonatus akibat ketidakcocokan Rh dapat berupa anemia hemolitik yang bisa sembuh sendiri hingga hidrops fetalis berat. Inkompatibilitas Rh dapat dicegah dengan pemberian terapi injeksi anti-D yang mengandung Rh Intravenous Immunoglobulin (RhIVIG). Kami melaporkan kasus langka dengan hasil perinatal yang baik inkompatibilitas rhesus pada multigravida tanpa injeksi terapi anti-D akibat fenotip D yang lemah.Ilustrasi Kasus: Seorang wanita gravida 3, para 2 pada usia kehamilan 27 minggu dengan golongan darah Rh-negatif, yang sebelumnya tidak mengalami masalah kompatibilitas, datang ke fasilitas kami untuk pemeriksaan antenatal rutin. Suami mempunyai golongan darah Rh-positif dengan genotipe Dd (heterozigot), sehingga kemungkinan keturunannya mempunyai golongan darah Rh-positif sebesar 50%. Hasil laboratorium menunjukkan tes Coombs negatif dan fenotipe D lemah. Pasien belum pernah menerima suntikan terapi anti-D pada kehamilan ini dan dua kehamilan sebelumnya. Semua anaknya tidak menderita penyakit hemolitik pada neonatus. Hasil USG menunjukkan janin usia kehamilan 27 minggu berkembang baik tanpa cacat bawaan mayor. Hasil perinatal yang baik mungkin disebabkan oleh lemahnya fenotip D. Ibu hamil dengan fenotip D yang lemah memiliki antigen D yang lebih sedikit sehingga masih dapat menyebabkan sensitisasi Rh, namun tidak cukup menyebabkan komplikasi serius pada janin.Kesimpulan: Inkompatibilitas rhesus dengan fenotip D lemah dapat memberikan outcome perinatal yang baik tanpa terapi injeksi anti-D. Injeksi Anti-D tetap dapat diberikan untuk mencegah aloimunisasi Rh di kemudian hari.Kata kunci: Fenotip D lemah, Imunoglobulin Rh, Inkompatibilitas rhesus, Multigravida, Terapi injeksi anti-D